2008
DOI: 10.1016/j.cell.2008.11.003
|View full text |Cite
|
Sign up to set email alerts
|

A New Component in Synaptic Plasticity: Upregulation of Kinesin in the Neurons of the Gill-Withdrawal Reflex

Abstract: Summary To explore how gene products, required for the initiation of synaptic growth, move from the cell body of the sensory neurons to its presynaptic terminals, and from the cell body of the motor neuron to its postsynaptic dendritic spines, we have searched for anterograde transport machinery in both the sensory and motor neurons of the gill-withdrawal reflex of Aplysia. We found that the induction of long-term facilitation (LTF) by repeated applications of serotonin, a modulatory transmitter released durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 43 publications
5
96
0
Order By: Relevance
“…55 In a later study, we demonstrated that knockdown of ApKHC1 blocked the initiation of LTF; however, once the LTF is initiated, knockdown of ApKHC1 does not block persistence. 40 Knockdown experiments of ApMHC, actin-dependent molecular motor, and mRNA cargo of ApKHC1, also showed similar results on initiation and persistence of LTF. 52 Together, these studies suggest that during persistence of memory, synapses become autonomous with respect to transport from the cell body, and RNAs are stored at the synapses for later use.…”
Section: When and How Are The Synaptically Localizedmentioning
confidence: 49%
See 1 more Smart Citation
“…55 In a later study, we demonstrated that knockdown of ApKHC1 blocked the initiation of LTF; however, once the LTF is initiated, knockdown of ApKHC1 does not block persistence. 40 Knockdown experiments of ApMHC, actin-dependent molecular motor, and mRNA cargo of ApKHC1, also showed similar results on initiation and persistence of LTF. 52 Together, these studies suggest that during persistence of memory, synapses become autonomous with respect to transport from the cell body, and RNAs are stored at the synapses for later use.…”
Section: When and How Are The Synaptically Localizedmentioning
confidence: 49%
“…Indeed, several synaptic proteins required for synapse formation (e.g., neurexin, neuroligin, piccolo, and bassoon) were found in the kinesin complex isolated from the CNS, which are required for the establishment of LTF. 39,40 Next, we searched for RNAs in the ApKHC1 complexes isolated from the Aplysia CNS. Since kinesin is the major motor that mediates the microtubuledependent transport of gene products from the cell body to distal neuronal processes, we assumed that molecular characterization of the kinesin complex would identify RNAs transported to synapses.…”
Section: Is the Kinesin-mediated Transport Of Proteins And Rnas Impormentioning
confidence: 99%
“…1A) following a previously published protocol (13) and analyzed by silver stain and Western blot analysis (Fig. 1B).…”
Section: Isolation and Characterization Of Protein Complexes Of Molecmentioning
confidence: 99%
“…To identify actively transported proteins, we focused on the protein complexes associated with kinesins, molecular motor proteins that move from the cell body to distal neuronal processes and mediate the transport of various gene products (9,13). We considered that proteins associated with kinesins include both synaptic proteins and proteins localized to dendrites and axons.…”
mentioning
confidence: 99%
“…Because the CNS contains both neuronal and nonneuronal cells, this approach will also yield RNAs found in the kinesin complex in nonneuronal cells, such as glia. We first optimized conditions for isolating RNA transport complexes from the CNS of Aplysia based on a previously described protocol for preparation of kinesin transport complexes Aplysia Kinesin Heavy Chain 1 (ApKHC1) that contain several synaptic proteins (15). To examine whether the transport complexes prepared from CNS contain RNA cargos ( Fig.…”
Section: Strategy For Identifying Synaptically Targeted Rnas: Isolatimentioning
confidence: 99%